Production of Sm-153 With Very High Specific Activity for Targeted Radionuclide Therapy - Van de Voorde, Michiel; Duchemin, Charlotte; Heinke, Reinhard; Lambert, Laura; Chevallay, Eric; Schneider, Thomas; Van Stenis, Miranda; Cocolios, Thomas Elias; Cardinaels, Thomas; Ponsard, Bernard; Ooms, Maarten; Stora, Thierry; et al. (Frontiers in Medicine, 2021)
Samarium-153 (153Sm) is a highly interesting radionuclide within the field of targeted radionuclide therapy because of its favorable decay characteristics. 153Sm has a half-life of 1.93 d and decays into a stable daughter nuclide (153Eu) whereupon β− particles [E = 705 keV (30%), 635 keV (50%)] are emitted which are suitable for therapy. 153Sm also emits γ photons [103 keV (28%)] allowing for SPECT imaging, which is of value in theranostics. However, the full potential of 153Sm in nuclear medicine is currently not being exploited because of the radionuclide's limited specific activity due to its carrier added production route. In this work a new production method was developed to produce 153Sm with higher specific activity, allowing for its potential use in targeted radionuclide therapy. 153Sm was efficiently produced via neutron irradiation of a highly enriched 152Sm target (98.7% enriched, σth = 206 b) in the BR2 reactor at SCK CEN. Irradiated target materials were shipped to CERN-MEDICIS, where 153Sm was isolated from the 152Sm target via mass separation (MS) in combination with laser resonance enhanced ionization to drastically increase the specific activity. The specific activity obtained was 1.87 TBq/mg (≈ 265 times higher after the end of irradiation in BR2 + cooling). An overall mass separation efficiency of 4.5% was reached on average for all mass separations. Further radiochemical purification steps were developed at SCK CEN to recover the 153Sm from the MS target to yield a solution ready for radiolabeling. Each step of the radiochemical process was fully analyzed and characterized for further optimization resulting in a high efficiency (overall recovery: 84%). The obtained high specific activity (HSA) 153Sm was then used in radiolabeling experiments with different concentrations of 4-isothiocyanatobenzyl-1,4,7,10-tetraazacyclododecane tetraacetic acid (p-SCN-Bn-DOTA). Even at low concentrations of p-SCN-Bn-DOTA, radiolabeling of 0.5 MBq of HSA 153Sm was found to be efficient. In this proof-of-concept study, we demonstrated the potential to combine neutron irradiation with mass separation to supply high specific activity 153Sm. Using this process, 153SmCl3 suitable for radiolabeling, was produced with a very high specific activity allowing application of 153Sm in targeted radionuclide therapy. Further studies to incorporate 153Sm in radiopharmaceuticals for targeted radionuclide therapy are ongoing.